Congenital Cytomegalovirus Infection in a Neonate with Severe Clinical Complications: A Case Report. - Siddique, Md. Abu Baker; Akram, Arifa; Nafisa, Tasnim; Resma, Tania Islam (Bangladesh Journal of Infectious Diseases, 2025)
Worldwide, cytomegalovirus (CMV) is a major cause of congenital infections that can result in a variety of clinical symptoms, especially in newborns. In this case study, a 2-month-old child was found to have a high CMV viral load in her urine sample using PCR testing. Her complicated medical history included neonatal convulsions, cyanosis, pneumonia, fever, and lymphadenopathy. She was born at home. In addition to examining the difficulties in managing neonates and optimizing outcomes, this report emphasizes the significance of prompt identification and treatments for congenital CMV, particularly in environments with limited resources. Bangladesh Journal of Infectious Diseases, December 2024;11(2):205-208